2019
DOI: 10.4103/jisp.jisp_506_18
|View full text |Cite
|
Sign up to set email alerts
|

Impact of periodontal knowledge and attitude on the status of the periodontium: A profile on West Godavari district, Andhra Pradesh, India

Abstract: Background: Although regular patient education regarding the periodontal health/disease is advocated as a means of improving oral health, impregnable associations of periodontal knowledge and attitude with periodontal status have not been demonstrated. Materials and Methods: In a cross-sectional study conducted, 2400 participants were surveyed using a specially designed pretested pro forma to evaluate the knowledge and attitude concerning periodontal health and disease.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…In contrast, another crosssectional study investigated the impact of knowledge and attitude on the status of periodontium among an Indian population and reported a good knowledge level among majority of the study participants regarding the role of dental plaque and its causation to periodontal disease. The authors attributed this high knowledge score to the adequate health education programs that were regularly performed by the dental institutes within the study area (Penmetsa et al, 2019). Furthermore, most of the present study participants had a good knowledge towards the positive role of oral hygiene measures and regular dental visits in prevention of periodontal disease, a finding which was also reported in previous studies (Taani, 2002, Deinzer et al, 2009, Gholami et al, 2014, Allam et al, 2020.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In contrast, another crosssectional study investigated the impact of knowledge and attitude on the status of periodontium among an Indian population and reported a good knowledge level among majority of the study participants regarding the role of dental plaque and its causation to periodontal disease. The authors attributed this high knowledge score to the adequate health education programs that were regularly performed by the dental institutes within the study area (Penmetsa et al, 2019). Furthermore, most of the present study participants had a good knowledge towards the positive role of oral hygiene measures and regular dental visits in prevention of periodontal disease, a finding which was also reported in previous studies (Taani, 2002, Deinzer et al, 2009, Gholami et al, 2014, Allam et al, 2020.…”
Section: Discussionsupporting
confidence: 86%
“…data regarding periodontal health knowledge and practice is available from numerous countries in the world. Data from Saudi Arabia, Syria and Lebanon have shown that adults with completely healthy periodontal tissues comprise a small minority of their population (Gholami et al, 2014, Nyorobi et al, 2018, Zhao et al, 2019, Penmetsa et al, 2019. However, little published data is available on the level of periodontal knowledge and its impact on the state of periodontal health among the eastern Mediterranean countries (El-Qaderi and Quteish Ta'ani, 2004, Gholami et al, 2014, Penmetsa et al, 2019.…”
Section: Epidemiologicalmentioning
confidence: 99%
“…The low level of utilization of oral and dental health services causes a high level of oral and dental diseases in the community. 9 Other factors which influence the utilization of oral and dental health services is perception towards the need for certain health service and assessment towards the need for or benefits of such service. 10 The chi-square analysis result shows that there is a relationship between the OHI-S index and periodontal disease (p<0.05 3).…”
Section: Materials Andmethodsmentioning
confidence: 99%
“…As an effort to prevent and promote health about periodontal disease cases, the level of knowledge and attitude about periodontal disease is very important to give in such a young age [17]. It has been proven that high knowledge level scores in some populations influence the incidence of periodontal disease in that population [17]. Adequately, this is supported by a proper health education program in formal and non-formal stage [17].…”
Section: The Effect Analysis Of the Level Of Knowledge On Periodontalmentioning
confidence: 99%
“…It has been proven that high knowledge level scores in some populations influence the incidence of periodontal disease in that population [17]. Adequately, this is supported by a proper health education program in formal and non-formal stage [17].…”
Section: The Effect Analysis Of the Level Of Knowledge On Periodontalmentioning
confidence: 99%